Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di RSUD Linggajati Kuningan - Neneng Sriyani; Dewi Erna Marisa (Jurnal Sehat Indonesia (JUSINDO), 2022)
Chronic kidney failure or end-stage renal disease (ESRD) is a progressive and irreversible renal function disorder, where kidney function decreases in maintaining metabolism, fluid and electrolyte balance, resulting in uremia (retention of urea and other nitrogenous wastes in the blood. This study used a descriptive approach to hemodialysis patients at Linggarjati Kuningan Hospital. The population and sample are 49 respondents. The results of the study on the Quality of Life of Chronic Kidney Failure Patients Undergoing Hemodialysis at the Linggajati Kuningan Hospital showed the quality of life of the majority of respondents were in bad condition, namely 30 people (61%) and 19 people (39%). The results showed the quality of life based on the physical dimensions of the majority in the bad category as much as 55.1%, based on the psychological health dimensions the majority in the bad category as much as 57.3%. While the category of social relations is in the good category as much as 51% and the environmental dimension as much as 53.1%.